Study on the relationship between microstructure and tensile mechanical behavior of Hastelloy X foil - Hua Yu; Xin Li; He Jiang; Jianxin Dong (Journal of Materials Research and Technology)
To support the microstructure and performance design of 0.05 mm Hastelloy X alloy foil, the influence of microstructural features on its room-temperature tensile behavior was investigated through a combination of experimental testing and crystal plasticity simulations. The results demonstrate that the synergistic refinement of grains and carbides is critical for simultaneously enhancing the strength and toughness of the alloy foil. In contrast, the presence of coarse grains and carbides promotes strain localization and early void formation, leading to degraded mechanical performance. The dominant deformation mechanism in the foil is consistent with that of bulk Hastelloy X alloys and is primarily governed by dislocation slip. Finer grains promote more homogeneous plastic deformation. Simulation results further reveal that grain size plays a more significant role than carbides in achieving uniform deformation. Regarding damage behavior, finer carbides effectively suppress early cracking and void nucleation, thereby enhancing the damage resistance of the alloy foil.